Targeting angiogenesis in metastatic renal cell carcinoma. Issue 3 (4th March 2019) - Canino, Costanza; Perrone, Lorenzo; Bosco, Eugenia; Saltalamacchia, Giuseppe; Mosca, Alessandra; Rizzo, Mimma; Porta, Camillo
ABSTRACT: Introduction : Renal cell carcinoma (RCC), and particularly its clear cell histological subtype, is commonly characterized by genetic alterations in the Von Hippel Lindau ( VHL ) tumor suppressor gene, leading to a typically exasperated angiogenesis. However, other biological and genetic peculiarities contribute to differentiate this malignancy from other solid tumors, including its immunogenicity. Areas covered : This review focuses on the present and future role of antiangiogenic drugs, administered either alone (as it has been in the past few years), or in combination with other agents (e.g. immune checkpoint inhibitors), in the treatment of metastatic RCC. Expert commentary : Due to its peculiar pathogenesis, it is unrealistic to expect to be able to get rid of antiangiogenic agents for the treatment of this disease; however, we do expect that combinations of VEGF/VEGFRs-targeting agents with immune checkpoint inhibitors will gradually replace antiangiogenic monotherapies as the standard of care, at least in the first line setting of metastatic RCC patients. Biomarkers discovery remains the highest priority in order to further improve the percentage of patients benefitting of our treatment.